Prenatal diagnosis and molecular cytogenetic characterization of an inherited microdeletion of 18q12.3 encompassing SETBP1. Issue 9 (September 2022) - Zhou, Yaqing; Quan, Yan; Wu, Yijun; Zhang, Yinxing
The 18q12.3 region contains the SET binding protein 1 (SETBP1) gene. SETBP1 mutations or deletions are associated with Schinzel–Giedion syndrome or intellectual developmental disorder, autosomal dominant 29. We report the prenatal diagnosis and genetic counseling of a patient with a maternally inherited 18q12.3 microdeletion. In this family, the mother and son carried the same microdeletion. Chromosomal microdeletions and microduplications are difficult to detect using conventional cytogenetics, whereas the combination of prenatal ultrasound, karyotype analysis, chromosomal microarray analysis, and genetic counseling is helpful for the prenatal diagnosis of chromosomal microdeletions/microduplications.